Immunity Against Leishmania major Infection: Parasite-Specific Granzyme B Induction as a Correlate of Protection - Boussoffara, Thouraya; Chelif, Sadok; Ben Ahmed, Melika; Mokni, Mourad; Ben Salah, Afif; Dellagi, Koussay; Louzir, Hechmi (Frontiers in Cellular and Infection Microbiology, 2018)
Zoonotic cutaneous leishmaniasis (ZCL) caused by Leishmania (L.) major infection is characterized by different clinical presentations which depend in part on the host factors. In attempt to investigate the impact of the host’s immune response in the outcome of the disease, we conducted a prospective study of 453 individuals living in endemic foci of L. major transmission in Central Tunisia. Several factors were assessed at the baseline including (i) the presence of typical scars of ZCL, (ii) in vivo hypersensitivity reaction to leishmanin and (iii) the in vitro release of granzyme B (Grz B) by peripheral blood mononuclear cells (PBMC) in response to stimulation with live L. major promastigotes. After one season of parasite’s transmission, repeated clinical examinations allowed us to diagnose the new emerging ZCL cases. Heterogeneity was observed in terms of number of lesions developed by each individual as well as their size and spontaneous outcome, which led us to establish the parameter "severity of the disease". The efficacy of the presence of typical ZCL scar, the leishmanin skin test (LST) positive reactivity and the high levels of Grz B (≥2 ng/ml), in the protection against the development of ZCL were 29%, 15% and 22%, respectively. However, these factors were more efficient against development of intermediate or severe forms of ZCL. Levels of Grz B greater than 2ng/ml showed the best efficacy of protection (equals to 72.8%) against development of these forms of ZCL. The association of such parameter with the positivity of the LST exhibited a better efficacy (equals to 83.6%). In conclusion, our results support the involvement of Leishmania-specific cytotoxic cellular immune response in host protection against Leishmania-infection. This factor could be of great interest in monitoring the success of vaccination against human leishmaniasis.